PENGARUH KUALITAS ITEM TERHADAP RELIABILITAS ALPHA CRONBACH PADA TES BAKAT NUMERIKAL DAN TES POTENSI AKADEMIK - Jumailiyah, Jumailiyah (Jurnal Ilmiah IKIP Mataram, 2018)
The quality of the items in this study is limited to the level of difficulty and item discrimination in classical model and reliability test is Alpha Cronbach. Object of research is numerical standardized test consists of 18 groups and 12 groups of tests that have not been standardized each of 20 items,. Each group calculated Alpha Cronbach coefficient, the mean level of difficulty of the questions and the mean discrimination items. Testing the hypothesis is calculated by multiple regression analysis with SPSS ver PSAW. 18. The results obtained indicate, simultaneously the value of F = 67 625 (sig = 0.000), the effect of item difficulty level (Mean P) to the reliability of the value t = 2,949 (sig = 0.007) and the average impact biserial item (Mean bis) obtained t = 3,653 (sig = 0.001). In conclusion there is the influence of the quality of the items on Cronbach’s alpha coefficie.